Oil and Fat Production Waste and Its Use in Various Fields - Abdukarimova Dinara Nuritdinovna (Web of Journals Publishing, 2023)
The results of a study of the structures, compositions and physicochemical properties of gossypol resin and other ingredients are presented. The possibility of using them in the development of composite chemical preparations for treating cotton seeds has been shown.
Keywords: Chemical reagent, chemical technology, gossypol resin, caustic soda, sodium salts, carboxylic acids, carbolic acids, seed protectant.